RENIN AND ALDOSTERONE PRODUCTION IN CHILDREN WITH HYDRONEPHROSIS WITH RELATION TO THE SEVERITY OF NON-DIFFERENTIATED CONNECTIVE TISSUE DYSPLASIA AND TIME OF URINAL OBSTRUCTION ELIMINATION - A.M. Mambetova; R.A. Zhetichev; N.N. Shabalova; T.R. Indarokov (Вопросы современной педиатрии, 2011)
This article covers peculiarities of renin and aldosterone production in children with hydronephrosis with relation to the severity of non-differentiated connective tissue dysplasia (NDCTD) and time of urinal obstruction elimination. The grounds for this study are: the notion about hydronephrosis being an internal phenotypic indication of NDCTD, presence of NDCTD of various severity in all children with hydronephrosis, correlation between presence of moderate to severe NDCTD and nephrosclerosis formation, type and time of progression of different forms of renal pathology; modern conception of rennin and aldosterone participation not only in electrolyte balance regulation and vasomotion, but in fibrogenesis stimulation as well. Study objective — to evaluate renin and aldosterone production in children with hydronephrosis with relation to the severity of NDCTD and time of urinal obstruction elimination. 39 patients with hydronephrosis participated in the study. Groups were designed with relation to the severity of NDCTD and duration of the obstruction. The relation between rennin production and severity of NDCTD has been shown for the first time. Moderate to severe forms of NDCTD were accompanied with hyperreninaemia regardless the time of obstruction duration and are characterized by early nephrosclerosis formation, relapses of secondary pyelonephritis and renal failure progression. Hyperaldosteronism mostly reflects time of obstruction duration, also adds to srterisl hypertension formation, but is not clearly related to the severity of NDCTD.Key words: non-differentiated connective tissue dysplasia, renin, aldosterone. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (6): 35–40.)